Clinical presentation, diagnosis, treatment and outcome of spinal epidural empyema in four cats (2010 to 2016). (2nd November 2018) - Guo, S.; Lu, D.
Abstract : This case series reviews previous publications and reports four feline spinal epidural empyema cases that presented with non‐ambulatory thoracolumbar myelopathy. Two cats underwent myelography and two MRI. Bacteria were obtained in three cases, in two from epidural abscesses and from a tail base wound in one; histopathological examination of epidural tissue showed pyogranulomatous changes in the remaining cat. Three cats were treated by surgical decompression plus antimicrobial therapy and one cat was treated medically. All cats showed satisfactory improvement following treatment over a follow‐up period of 3 months. Spinal epidural empyema is a rare condition but all cats in this series had favourable outcomes.